Cálculo da temperatura no interior de uma placa com auxílio do método das diferenças finitas - Lobeiro, Adilandri Mércio (2014)
This paper addresses the analysis of the efficiency of the Finite Difference Method when applied to a common problem of physics and engineering: the temperature distribution along a thin, square plate. The paper contains a description of the numerical method, including its deduction and way of application, highlighting its praticality and ease of use, aiming to incentivate its use and dissemination. Futhermore, there is an introduction to the Poisson’s equation, whose solution represents the value of the temperature at each point in the interior of the plate under certain conditions. An algorithm was implemented and applied in the resolution of a case study.